Antibacterial and anti-biofilm activity of radezolid against Staphylococcus aureus clinical isolates from China - Wang, Cong; Xiong, Yanpeng; Bao, Chai; Wei, Ying; Wen, Zewen; Cao, Xinyi; Yu, Zhijian; Deng, Xiangbing; Li, Guiqiu; Deng, Qiwen (Frontiers in Microbiology, 2023)
Although the potent antibacterial ability of radezolid against Staphylococcus aureus has been widely reported worldwide, its antibacterial and anti-biofilm activity against the S. aureus clinical isolates from China remains elusive. In this study, the minimum inhibitory concentration (MIC) of radezolid was determined in S. aureus clinical isolates from China using the agar dilution method, and the relationship between radezolid susceptibility and ST distribution was also investigated. The anti-biofilm activity of radezolid against S. aureus was determined by a crystal violet assay and compared with that of linezolid and contezolid. The quantitative proteomics of S. aureus treated with radezolid was analyzed, and the genetic mutations in radezolid-induced resistant S. aureus were determined by whole-genome sequencing. The dynamic changes in transcriptional expression levels of several biofilm-related genes were analyzed by quantitative RT-PCR. Our data showed that radezolid MIC ranged from ≤0.125 to 0.5 mg/L, which was almost 1/4 × MIC of linezolid against S. aureus, indicating the greater antibacterial activity of radezolid than linezolid. The S. aureus clinical isolates with radezolid MICs of 0.5 mg/L were most widely distributed in ST239 of MRSA and ST7 of MSSA. Moreover, the more robust anti-biofilm activity of radezolid with subinhibitory concentrations (1/8 × MIC and 1/16 × MIC) was demonstrated against S. aureus when compared with that of contezolid and linezolid. Genetic mutations were found in glmS, 23S rRNA, and DUF1542 domain-containing protein in radezolid-induced resistant S. aureus selected by in vitro induction of drug exposure. Quantitative proteomic analysis of S. aureus indicated that the global expression of some biofilm-related and virulence-related proteins was downregulated. Quantitative RT-PCR further confirmed that the expressions of some downregulated biofilm-related proteins, including sdrD, carA, sraP, hlgC, sasG, spa, sspP, fnbA, and oatA, were decreased after 12 h and 24 h of exposure to radezolid. Conclusively, radezolid shows robust antibacterial and anti-biofilm activity against S. aureus clinical isolates from China when compared with contezolid and linezolid.